Molecular pathophysiology of acute kidney injury: The role of sirtuins and their interactions with other macromolecular players. Issue 5 (28th September 2020) - Rahbar Saadat, Yalda; Hosseiniyan Khatibi, Seyed Mahdi; Ardalan, Mohammadreza; Barzegari, Abolfazl; Zununi Vahed, Sepideh
Abstract: Acute kidney injury (AKI), a rapid drop in kidney function, displays high mortality and morbidity, and its repeated or severe status can shift into chronic kidney disease or even end‐stage renal disease. How and which events cause AKI still is controversial. In addition, no specific therapies have emerged that can attenuate AKI or expedite recovery. Some central mechanisms including tubular epithelial cells injury, endothelial injury, renal cell apoptosis, and necrosis signaling cascades, and inflammation have been reported in the pathophysiology of AKI. However, the timing of the activation of each pathway, their interactions, and the hierarchy of these pathways remain unknown. The main molecular mechanisms that might be complicated in this process are the mitochondrial impairment and alteration/shifting of cellular metabolites (e.g., acetyl‐CoA and NAD + /NADH) acting as cofactors to alter the activities of many enzymes, for instance, sirtuins. Moreover, alteration of mitochondrial structure over the fusion and fission mechanisms can regulate cellular signaling pathways by modifying the rate of reactive oxygen species generation and metabolic activities. The aim of this review is to better understand the underlying pathophysiological and molecular mechanisms of AKI. In addition, we predicted the main other molecular players in interaction with sirtuins as energy/stresses monitoring proteins for the development of future approaches in the treatment or prevention of ischemic AKI. Abstract : Mitochondrial dysfunction and energy metabolism pathways are serious drivers of acute kidney injury (AKI). Sirtuins overexpression can guard kidney cells against AKI by hindering apoptosis, inducing mitochondrial biogenesis and autophagy, which may become new approaches to the prevention and treatment of AKI.